2022
DOI: 10.1088/1361-6463/ac406a
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporally resolved measurements of electric field around a piezoelectric transformer using electric-field induced second harmonic (E-FISH) generation

Abstract: When a piezoelectric transformer (PT) is actuated at its second harmonic frequency by a low input voltage, the generated electric field at the distal end can be sufficient to breakdown the surrounding gas, making them attractive power sources for non-equilibrium plasma generation. Understanding the potential and electric fields produced in the surrounding medium by the PT is important for effectively designing and using PT plasma devices. In this work, the spatiotemporally resolved characteristics of the elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…The enhanced HH spectrum is absent in the multipactor-dominant stage, for example 0 < t/T < 6 at the base case, and it appears only in the transition from multipactor to rf plasma, where the plasma density is around 10 20 to 10 21 m −3 , thus, the detection of the enhanced HH spectrum has a potential to be a indicator for ionization breakdown in multipactor-coexisting plasma breakdown process at similar external conditions, i.e., the gas pressure is tens to hundreds of mTorr and rf frequency around 0.5-2 GHz. In addition, the fast-oscillating HH field is expected to be potentially measured in experiments by the femtosecond E-FISH [51], i.e., electric field-induced second harmonic generation method, that provides a resolution of sub-nano second in time and sub-millimeter in space for an electric field component in a given direction.…”
Section: Concluding Remarks and Discussionmentioning
confidence: 99%
“…The enhanced HH spectrum is absent in the multipactor-dominant stage, for example 0 < t/T < 6 at the base case, and it appears only in the transition from multipactor to rf plasma, where the plasma density is around 10 20 to 10 21 m −3 , thus, the detection of the enhanced HH spectrum has a potential to be a indicator for ionization breakdown in multipactor-coexisting plasma breakdown process at similar external conditions, i.e., the gas pressure is tens to hundreds of mTorr and rf frequency around 0.5-2 GHz. In addition, the fast-oscillating HH field is expected to be potentially measured in experiments by the femtosecond E-FISH [51], i.e., electric field-induced second harmonic generation method, that provides a resolution of sub-nano second in time and sub-millimeter in space for an electric field component in a given direction.…”
Section: Concluding Remarks and Discussionmentioning
confidence: 99%
“…For a mesoscopic unitary volume, the induced total dipole moment at the second harmonic frequency P 2ω expressed as a sum of two terms : P 2ω ∝ χ (2) (2ω, ω, ω) : E ω E ω + χ (3) (2ω, ω, ω, 0) : E ω E ω E DC , (1) where E ω is the exciting electromagnetic field at the fundamental frequency, and E DC is the external electrostatic field that potentially modifies (i) the orientation of dipoles, and (ii) the electronic-dependent molecular intrinsic SHG response. More recently, EFISHG has received renewed interest as a non-intrusive tool for probing electric fields in diluted media with spatial and temporal definition, using laser pulses 11 .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, EFISHG has received renewed interest as a nonintrusive tool for probing electric fields in diluted media with spatial and temporal definition, using laser pulses. 11 Eqn (1) was also applied to condensed phases, 12,13 and the EFISHG is an established technique to determine the first and the second hyperpolarizabilities of compounds in solutions. 14 Even more, studies on liquid/solid or liquid/air interfaces have reported the evolution of the Surface-SHG (S-SHG) response when the surface charge is modulated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent few decades, homochiral metal–organic frameworks (HMOFs) have gained significant momentum because of their diverse structure types, unique chiroptical properties, and extensive applications in asymmetric catalysis, optoelectronics, optical devices, and chiral recognition and separation. The most common approach to obtain HMOFs is the direct use of enantiopure chiral ligands, that is, enantiopure chiral ligands bridge metal ions to form various HMOF materials, and the ligands’ chirality can transmit into the whole network in this manner. , Nonlinear optical (NLO) materials have achieved more and more attention since their application prospects in many significant domains, such as biological tissue imaging, precise micromanufacturing, and information storage. Natural chiral amino acids and their derivatives are attractive organic NLO materials owing to their strong optical nonlinearity, easy chemical modification, wide transparency over an extensive frequency range, and lower UV cutoff edge. However, these organic NLO materials have the disadvantages of a low melting point, low hardness, and poor thermal stability, which greatly limit their applications in the field of hi-tech non-linear optics and photonics. For example, it is important to assess the thermal stability of NLO materials because it has a key impact on the laser damage threshold of NLO materials.…”
Section: Introductionmentioning
confidence: 99%